Implementing CRANE: a tool for simple deployment of containerized applications in local environments - Silva Pavón, José Miguel (2024)
CRANE is a tool designed for local deployment of containerized applications to simplify testing of locally distributed environments. CRANE's design offers a lightweight, general-purpose solution with automatic scaling capabilities, oriented to students and developers who need to create and deploy complete application stacks within a controlled environment. CRANE is also intended to facilitate the incorporation of DevOps skills, which accelerates the software development process in a continuous delivery framework.